Magnetic and dielectric properties of BaFe1/2Sn1/2O3-δ ceramics. Issue 6 (15th March 2022) - Bikyashev, E.A.; Popov, A.V.; Kubrin, S.P.; Yanda, Premakumar; Mayorov, M.B.; Trigub, A.; Shuvaeva, V.A.; Sundaresan, A.; Raevski, I.P.; Ter-Oganessian, N.V.
Abstract: Ceramic samples of barium ferrostannate BaFe1/2 Sn1/2 O3-δ have been prepared by the sol-gel and hydrothermal synthesis methods. To reduce the number of oxygen vacancies, annealing in oxygen has been performed. The heat capacity, magnetization, Mössbauer and dielectric spectroscopy data point to the appearance of antiferromagnetic ordering below ∼55 K followed by further spin glass magnetic ordering below 15 K. The giant dielectric response seems to be due to the relaxation of electrons trapped by oxygen vacancies. Comparison of the Fe K-edge X-ray absorption spectra of BaFe1/2 Sn1/2 O3-δ confirmed substantial difference from those of the similar stoichiometric BaFe1/2 Nb1/2 O3 perovskite.